2020
DOI: 10.3390/cancers12113173
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying PD-L1 Expression to Monitor Immune Checkpoint Therapy: Opportunities and Challenges

Abstract: Therapeutics targeting programmed death ligand 1 (PD-L1) protein and its receptor PD-1 are now dominant players in restoring anti-tumor immune responses. PD-L1 detection by immunohistochemistry (IHC) is emerging as a reproducible biomarker for guiding patient stratification for those therapies in some cancers. However, PD-L1 expression in the tumor microenvironment is highly complex. It is upregulated by aberrant genetic alterations, and is highly regulated at the transcriptional, posttranscriptional, and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 177 publications
(225 reference statements)
0
52
0
Order By: Relevance
“…PD-1 activation regulates T cell activation, tolerance, and exhaustion, and effector T cell responses. 241,242 Programed death ligand 1 expression can predict a favorable response to antibodies designed to unfetter anti-tumor activity. 243 This means that PD-L1 and its receptor PD-1 represent crucial therapeutic targets to treat cancer as immune checkpoints regulating host immunity.…”
Section: Hormone-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-1 activation regulates T cell activation, tolerance, and exhaustion, and effector T cell responses. 241,242 Programed death ligand 1 expression can predict a favorable response to antibodies designed to unfetter anti-tumor activity. 243 This means that PD-L1 and its receptor PD-1 represent crucial therapeutic targets to treat cancer as immune checkpoints regulating host immunity.…”
Section: Hormone-based Therapiesmentioning
confidence: 99%
“…They reported that PD-L1 was predictive in only 28.9% of cases and was either not predictive (53.3%) or not tested (17.8%) in the remaining cases. 253 A broad review on this topic has been published by Nimmagadda 241 and Cottrell and Taube. 243 Nonetheless, fortunately, numerous IHC assays have been approved [254][255][256] to detect PD-L1 expression levels for specific drugs; each ICI has its own IHC assay specific to a distinct anti-PD-L1 antibody clone and a particular staining platform with specific tumor cell or immune cell thresholds.…”
Section: Hormone-based Therapiesmentioning
confidence: 99%
“…Anti-programmed death 1 activation can stimulate the upregulation of GLUT messenger RNA and GLUT proteins in the tumor microenvironment, leading to glucose consumption and increasing false-positive scanning results (81). The feasibility of using PET to quantify programmed death ligand 1 (PD-L1) levels in patients has been demonstrated with 89 Zr-labeled atezolizumab, but this method still has a high chance of false-positive results, possibly due to inflammation (82). Although there are ongoing clinical trials, there is currently no approved clinical imaging technique for tracking immune cells in humans.…”
Section: Imaging Applications In Monitoring Responses To Immunotherapymentioning
confidence: 99%
“…Therefore, blocking PD-1 enhances the antitumor activity of the immune system [15]. Studies related to the CTLA-4 protein and the PD-1 receptor are among the most relevant to the treatment of cancer and therefore, many recent reviews in leading biomedical journals have been published [6,14].…”
Section: Introductionmentioning
confidence: 99%